2023
DOI: 10.47191/ijsshr/v6-i4-62
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Collaborative Project and E-Portfolio in an Online Graduate Course: A Case Study

Abstract: The ability to work in teams is an imperative competency in today’s complex healthcare delivery system. Collaborative learning allows students to cultivate teamwork, communication, critical thinking, and problem-solving skills. Collaborative learning activity is an essential pedagogical approach to prepare students to meet the need of the healthcare workforce. This paper presents a research study in which a collaborative project was implemented in a redesigned healthcare administration course in an online grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Previously, we evaluated the students' perceptions about the ePortfolio assignment in the first course of integrating ePortfolio. The research findings from the first course showed that 60% of students felt that ePortfolio helped them start organizing the evidence of their accomplishments (Lu & Gustavus, 2023). However, in the current study, the survey question regarding ePortfolio gained the lowest score among all survey items at 75.7%, a 15.7 percent point increase from the first course of integrating ePortfolio.…”
Section: Resultscontrasting
confidence: 65%
“…Previously, we evaluated the students' perceptions about the ePortfolio assignment in the first course of integrating ePortfolio. The research findings from the first course showed that 60% of students felt that ePortfolio helped them start organizing the evidence of their accomplishments (Lu & Gustavus, 2023). However, in the current study, the survey question regarding ePortfolio gained the lowest score among all survey items at 75.7%, a 15.7 percent point increase from the first course of integrating ePortfolio.…”
Section: Resultscontrasting
confidence: 65%